Epidemiologic perspective of diarrheal disease in Costa Rica and current efforts in control, prevention and research - Mata Jiménez, Leonardo (1981)
artículo -- Universidad de Costa Rica, Instituto de Investigaciones en Salud (INISA), 1981.